The Role of Iran’s «Soft Power» in Confronting Iranophobia - S. M. Mirmohammad Sadeghi; R. Hajimineh (Vestnik MGIMO-Universiteta)
«Soft power» is a set of activities designed by a government or regional and international actors aimed to influence external public opinion, promote external image or attract support for a particular policy, which is implemented through all the available tools and new technologies. The non-governmental actors also play an effective and important role in this diplomacy. Considering the public diplomacy and soft power of the Islamic Republic of Iran as a deliberate and conscious approach can be of great importance in the country's grand strategies that will strengthen national interests in the domestic sphere and influence them at regional and global levels. The article analyzes the role of Iran’s soft power in confronting Iranophobia. The study is aimed at presenting a theoretical definition of public diplomacy and soft power in foreign policy and international system, and then examines its role in the foreign policy of the Islamic Republic of Iran with an emphasis on confronting Iranophobia.The authors answer the research question: “What is the role of soft power in the foreign policy of the Islamic Republic of Iran in confronting Iranophobia?” The research method is descriptive-analytical based on historical evidence, documents, and analytical issues of theorists, authors, and media being expressed in the theoretical framework of soft power. The paper is based on a synthesis of Stephen Walt’s “balance of threat” theory with Alexander Wendt’s social constructivism to explain the Iranian “threat” in American foreign policy.The findings of this research show that without the use of force and disturbing the balance in the international relations, using a variety of tools and instruments the Iranian public diplomacy and soft power might be effective to reduce the global and regional atmosphere of Iranophobia and undermine anti-Iranian solidarity.